2018
DOI: 10.1007/jhep02(2018)178
|View full text |Cite
|
Sign up to set email alerts
|

A global view on the Higgs self-coupling at lepton colliders

Abstract: We perform a global effective-field-theory analysis to assess the precision on the determination of the Higgs trilinear self-coupling at future lepton colliders. Two main scenarios are considered, depending on whether the center-of-mass energy of the colliders is sufficient or not to access Higgs pair production processes. Low-energy machines allow for ∼ 40% precision on the extraction of the Higgs trilinear coupling through the exploitation of next-to-leading-order effects in single Higgs measurements, provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 33 publications
3
113
0
Order By: Relevance
“…Equation (4.14), of 1, 1.1, 1.3 and 1.5 respectively. Also shown are contours corresponding to the 68% CL bounds from HL-LHC (dashed) and ILC-250 (dot-dashed), as found in [25]. baryon asymmetry can be otherwise enhanced, this scenario can be revived.…”
Section: Baryon Asymmetry With Modified Gauge Coupling Constantsmentioning
confidence: 99%
“…Equation (4.14), of 1, 1.1, 1.3 and 1.5 respectively. Also shown are contours corresponding to the 68% CL bounds from HL-LHC (dashed) and ILC-250 (dot-dashed), as found in [25]. baryon asymmetry can be otherwise enhanced, this scenario can be revived.…”
Section: Baryon Asymmetry With Modified Gauge Coupling Constantsmentioning
confidence: 99%
“…It counts 1 (δm) + 6 (hV V /aTGC) + 1 (aTGC) + 5 (hf f ) + 6 (Z ) + 3 (W ν) + 2 (Zuu) + 4 (Zdd) = 28 new physics parameters. Four-fermion operators that would be relevant for Drell-Yan production at high energies [43,44], or the trilinear Higgs self coupling that can be probed at tree level in di-Higgs production [16,45] and at the loop level in single Higgs processes [19,[46][47][48][49] are omitted from our analysis.…”
Section: Effective Field Theorymentioning
confidence: 99%
“…Our study extends and complements that of refs. [2,[12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We work in the context of the Warsaw basis [29], although one of the strengths of our approach is that it is straightforward to go from one basis to another. Several groups have performed global fits to determine the restrictions on SMEFT coefficients from LEP and LHC data [3,[5][6][7][8][9], with various assumptions to reduce the number of operators. In the future, such fits will need to become increasingly sophisticated as the amount of data increases.…”
Section: Effective Operatorsmentioning
confidence: 99%
“…To interpret Higgs measurements in a combined experimental and theory analysis we need to a) develop an efficient strategy to extract the maximum information from Higgs events, and b) publish this information in an efficient form. Many analyses focus on total rate measurements, but the available global fits have shown that kinematic information on new Lorentz structures provides the most powerful limits on new physics, for instance, exploiting the boosted regime of W H production [3,[5][6][7][8][9]. For the first aspect this means that total or fiducial rate measurements alone are not useful.…”
Section: Introductionmentioning
confidence: 99%